Verification of Spalling Tensile Strength of Rocks using 3D GPGPU-accelerated Hybrid FEM/DEM. Issue 1 (1st January 2023) - Min, G.; Fukuda, D.; Oh, S.; Liu, H.; Cho, S.
Abstract: The spalling test is widely applied for evaluating dynamic tensile strength of rock under high strain-rate condition. The dynamic tensile strength is indirectly measured in the spalling test by theoretically assuming the tensile stress level at the failure position of a cylindrical specimen based on the 1D stress wave propagation theory. However, the theoretical estimation method for dynamic tensile strength have not been fully validated since dynamic tensile strength was determined with insufficient understanding of the fracture process, such as crack propagation and stress distribution in the rock specimen during the spalling test, owing to observational limitations in the experiment. Thus, a proper validation method is required for the proposed method, and numerical simulation can be used to validate the proposed method by reproducing the tensile fracture process of the rock specimen during the spalling test. Thus, the dynamic spalling tensile test for rock specimens was reproduced in this study using the GPGPU-based 3D hybrid FDEM that we recently developed. The dynamic tensile fracturing process was analyzed in the simulation of spalling under various strain-rate conditions. Finally, we discussed the application of various theoretical estimation methods to the 3D spalling test.